Feasibility of post-stroke hand rehabilitation supported by a soft robotic hand orthosis in-clinic and at-home - Natalie Tanczak; Tegan Kate Plunkett; Sijie Lin; Lorena Kuenzler; Megan Lau; Wee Keong Christopher Kuah; Chwee Yin Ng; Roger Gassert; Karen Chua; Olivier Lambercy (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Stroke is a leading cause of adult disability in the world. Upper limb impairments are common post-stroke, with nearly half of those initially affected continuing to live with long-term functional limitations, impacting their independence and quality of life. Task-specific, intensive therapy has been shown to promote recovery; however, achieving this dose is resource-intensive and logistically challenging. Robotic hand orthoses (RHOs) are a promising approach to support functional rehabilitation regardless of location, thus providing high-dose therapy with minimal additional burden on the clinics. Methods We evaluated the use of the RELab tenoexo 2.0, a soft RHO, in a two-phase feasibility study supporting functional hand training in persons after chronic stroke. Participants (n = 8) first used the device to complete nine training sessions supervised by occupational therapists over 3 weeks in-clinic, then brought the device home to continue the training to complete 2 weeks of unsupervised training. Feasibility was assessed with therapy dose (repetitions and time) and adherence to the suggested at-home rehabilitation program. Functional improvements were tracked using clinical assessments across time points. Finally, usability evaluations provided insights into users’ perceptions of the device. Results During the in-clinic phase, participants completed an average of 809 ± 317 RHO supported repetitions over 521 ± 130 min. At home, this increased to 1293 ± 948 repetitions over 486 ± 125 min across an average of 11.75 ± 5.4 sessions. Across the whole intervention, participant’s mean Action Research Arm Test score increased by 5.0 ± 4.4, whereas the Fugl-Meyer Assessment Upper Extremity score increased by 6.0 ± 2.5. These improvements were retained after one month. The usability was rated as good, with a mean System Usability Scale rating of 72.5, and a mean Quebec User Evaluation of Satisfaction with Assistive Technology 2.0 score of 3.94/5.0. Conclusion This study shows that the RHO can serve as a viable rehabilitation tool for functional hand training after chronic stroke across the continuum of care. High-dose training, both in-clinic and at home, demonstrated the feasibility of the device and intervention, with meaningful clinical improvements highlighting its therapeutic potential as a training strategy. High adherence rates and positive usability indicate strong user acceptance. Trial registration NCT06412237